Using Nahr Umr Aquifer as an Additional Source of Injection Water for the X Oilfield - Almalikee, Hussein Saeed; Almayyahi, Hayder Kadhim; Al-Jafar, Methaq Khazal (Journal of Petroleum Research and Studies, 2022)
Water injection is the main strategy to increase oil production and support reservoirs pressure in the X oilfield and almost any other oilfield. The available source for the water injection in X field is the Qarmat Ali river which is located 20km to the north. However, the amount of water from that river is insufficient. Therefore, alternative water sources were investigated and among them, it was identified the Nahr Umr aquifer as the most promising. Nahr Umr is a regional giant aquifer; it is composed of high porous high permeable sandstone at an average depth of 2900m. The analysis of Nahr Umr aquifer water showed that it has a very high salinity (240000 ppm) almost composed of sodium and calcium chlorides, free of Oxygen, no solid particles were observed, no quantities of dissolved H2S, and very low occurrence of bacteria owing to the high water salinity and high temperature of the aquifer. On other hand, aquifer water contains a significant amount of dissolved CO2 (5.5%) which can cause corrosion. Therefore, there is a need to treat that water to decrease CO2 or use high corrosion-resistant materials in the pipelines and water source wells.